(3GdaSGO h CNdGbjGJ GdYed s - (3HhaGdWI(B, (3eMeO Sja GdOjfs ((3GdLRGFQs (3GdaG ddhKGFbs, 2022)
(3LhgQ GdaSGO h CfhGYg h eXGgQ GdaSGO GdGOGQj h GdeGdj , CSHGH GdaSGO GdEOGQj h GdeGdj h BKGQg , eMGQHI GdaSGO ef WQa GdgjFGJ h GdefXeGJ GdOhdjI h GdeMdjI , WQb YdGL GdaSGO h CHQR GdJLGQH GdOhdjI aj ecGaMJg h CNjQG CNdGbjGJ GdYed(B.s
Keywords: (3CNdGbjGJ GdYeds; (3GdaSGO GdGOGQjs